login
E.g.f. satisfies A(x) = 1 + x*A(x)*exp(x*A(x)^4).
2

%I #8 Nov 01 2024 09:30:18

%S 1,1,4,45,772,17865,525966,18794881,790175128,38221092657,

%T 2091074167450,127675964340441,8606833626646740,634928943628432921,

%U 50878715440232312374,4400937219238706030865,408700742920092110904496,40558224679468186878237153,4283310197644529184427059378

%N E.g.f. satisfies A(x) = 1 + x*A(x)*exp(x*A(x)^4).

%F a(n) = n! * Sum_{k=0..n} k^(n-k) * binomial(4*n-3*k+1,k)/( (4*n-3*k+1)*(n-k)! ).

%o (PARI) a(n) = n!*sum(k=0, n, k^(n-k)*binomial(4*n-3*k+1, k)/((4*n-3*k+1)*(n-k)!));

%Y Cf. A161633, A364980, A364981.

%Y Cf. A377551, A377552.

%K nonn

%O 0,3

%A _Seiichi Manyama_, Oct 31 2024